MONITORING OF RADIOACTIVE CONTAMINATION SOILS AND GROUND PRODUCTS ON THE TERRITORY OF THE INITIAL TOWN OF THE STATE BIOTECHNOLOGICAL UNIVERSITY UNIVERSITY (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
The main directions of research related to the accident at the Chernobyl NPP is given. The data from the gamma background and the level of radioactive contamination of agricultural lands of the educational and research farm of the KHNAU are presented. V. V. Dokuchaeva (now DBTU).It is shown that the increased values of the radiation background were recorded during the first three years after the accident, which is caused by radioactive fallout. The density of soil contamination with radioactive cesium increased from 0.02 to 0.5 Ki/km2, but their total pollution (137Cs + 90Sr) did not exceed 1 Ki/km2, which allows classifying the investigated soils into the "clean" category. A different pattern of radioactive contamination was observed in the Sumy region, which was chosen for comparison. Of course, different administrative regions were characterized by different degrees of pollution. Moreover, in different years at the same monitoring sites (Shostkinsky state farm named after Shchors, Shostka), quite significant differences in the density of pollution were observed 137Cs (0.32-0.90 Ki/km2). It is likely that the increase in radioactive soil contamination in 1991 is related to later releases of radioactivity. Radiometric data for the Donetsk and Kharkiv regions indicate that the specified territories belong to the category of clean zones.As of 1991, total pollution 137Cs and 90Sr in the soils of the Donetsk region did not exceed 0.06-0.13 Ki/km2.Monitoring of the radiation background on the territory of the educational campus indicates its significant increase in the post-accident period. Thus, the value of the radiation background measured on the "Beta" radiometer in 1985 was 1.33 imp/s. During the 90s, it varied between 2.03-2.48 imp/s. Its absolute values depended on the location of the measurement.Measurement of the radiation background in the dendrological park did not confirm the accumulation of radioisotopes by woody vegetation. If the radiation background near the 4th educational building of the university was 2.45 imp/s, then in the dendrological park – 2.36 imp/s.In 2023 - 2024, the radiation background on the territory of the educational campus was 11-12 μR/h, which indicates the absence of external radioactive contamination. Interesting data were obtained during radiation control of food products. As of 1991, the specific radioactivity of wheat bread was at the TDR level (1.0 x10-8). For rye bread, it exceeded the TDR and amounted to 1.59 x 10-8 Ki/kg. This is due to the cultivation of rye in the northern and western regions of Ukraine, where radioactive fallout occurred. 38 years after the accident, the situation stabilized and the specific radioactivity of bakery products did not exceed the permissible limits.
Keywords: продукти харчування; 137Cs; 90Sr; soils; food